Do they need to integrate? The place of EU citizens in the UK and the problem of integration. Issue 10 (27th July 2022) - Nancheva, Nevena; Ranta, Ronald
ABSTRACT: This article aims to provide empirical evidence against the theory and practice of immigrant integration through the experience of EU citizens in the UK around Brexit. We demonstrate that, in the case of EU citizens, the outcomes of presumably successful "integration" have been achieved while – and, we argue, because of the fact that – EU citizens have been treated as citizens (not migrants) and have been freed from the requirement to "integrate". On the basis of interviews, focus groups and a survey in the period 2016–18 we show meaningful incorporation of a variety of EU citizens of all backgrounds, including those from the so-called "low-skilled" presumably problematic to integrate subgroup. We claim that work, family, locality and time determine much of the intricacies of the incorporation journey. Integration governance which Brexit imposed on EU citizens can only threaten these outcomes.